Knowledge Management at Cory Environmental: A Theoretical and Empirical Analysis - Carter, Jonathan David (2007)
To answer the question "How can Cory make better use of existing knowledge and create the new knowledge necessary to improve company performance?", an analysis of knowledge management practice at Cory Environmental was carried out using the knowledge management enabler model (Girard 2004) as a framework. To keep the project manageable research was restricted to knowledge management in relation to the commercial sales function within Cory, but the assumption was that findings and recommendations here could be applied to other areas of the business with equal relevance. Improving knowledge management within Cory would lead to improvements in customer account management, tender preparation, and marketing and result in significant cost and time savings. Of the four enablers examined, leadership was found to be the most important within Cory. Primarily a lack of leadership understanding of and commitment to knowledge management meant that the other enablers; IT systems, processes and culture, were being negatively influenced either through a lack of financial or direct management support. Before any significant improvement in knowledge management can take place within Cory there will need to be a change in attitude amongst senior managers towards the importance of knowledge and the need to pro-actively manage it. Only if this can be achieved should Cory embark on implementing the recommendations for improvement made in this project paper.